Rebar welding at permanent caping in D-wall - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This variation order has been made between Brac University and BUCG-ABC joint venture for rebar welding at permanent caping in D-wall of Brac University new campus project.